Liberdade sindical brasileira: uma análise para avaliação e aperfeiçoamento das relações de trabalho - GAGLIANONE , Luciana Aguilera (2018)
Freedom of association configures a recurrent theme in national and international doctrine, so that strategies for its wide implementation in Brazil must be developed. In this comparison, the present study evaluates the effectiveness of union unity and compulsory union contribution in the scope of labor relations, and how these institutes influence union activity in the promotion of public policies for the improvement of labor relations and the generation of jobs. It analyzes whether union unity, coupled with compulsory financing, cooperate with the maintenance of corporatist remnants, hindering the progress of labor ties. It uses the methodology of compilation and exploration, through critical analysis of scientific positions and bibliographical research of scientific periodicals, analysis of books and philosophical works. It applies the deductive method, emphasizing the qualitative observation and the investigation of processes that have been processed (or processed) in the Brazilian Labor Courts, examining the measures and decisions adopted in each case and its reflexes. It concludes that there was no overcoming of criteria inherited from authoritarian regimes, despite the authorization granted by the international and constitutional norms that protect freedom of association, configuring union unity and compulsory union contribution obstacles to a positive trade union action, especially as regards to acts linked to the improvement of labor relations and the generation of jobs